Weather Variation and Child Health Outcomes in Nepal - Timsina, Maya (Journal of Development and Administrative Studies, 2019)
This study examines the relationship between weather variability and child health outcomes in Nepal. The results indicate that temperature deviations significantly impact malnutrition, not stunting and wasting in children under five. Rainfall deviations, on the other hand, do not show a significant association with malnutrition. However, rainfall variability caters to mortality rates, while temperature deviations do not. The study suggests considering climatic variability in child health policy crafting in Nepal. Further studies that consider the climate and socioeconomic heterogeneity might serve better.